Infraspecific phenotypic variation of the California Quail (Callipepla californica, Aves: Odontophoridae) from Baja California peninsula, Mexico - María Cabrera-Huerta; Gorgonio Ruiz-Campos; Horacio De la Cueva; Philip Unitt; Francisco J. García-De León (Huitzil, 2018)
To determine useful diagnostic characters for infraspecific taxonomic identification of California Quail (Callipepla californica) from Baja California peninsula, we compared phenotypically four nominal subspecies by means of multivariate statistical analysis of 18 variables: nine morphometric and nine chromatic. We examined 338 museum specimens from 114 sites, and compared using two categories: subspecies and type locality. The principal components analysis (PCA) did not showed congruent groups with known taxonomic subspecies in spite of that characters associated to the measurements of peak and coloration in both sexes had a significant discriminant power. Discriminant function analysis (AFD) found significant differences in the a priori comparison categories, P <0.05. Phenotypically, the distinction of subspecies (C.c. californica, C.c. plumbea, C.c. decolorata and C.c. achrustera) was only possible in its type localities. The males are separated by the culmen length, jaw length, brightness of the chest and flank, and yellow patch, while the females by the beak length, wing length, and jaw length. In summa, the results obtained are not sufficient evidence for the validation or rejection of the nominal subspecies, so the presence of a mosaic pattern in the phenotypic variation of the populations could explain the observed morphometric and colorimetric differences.